Regulation of CD47 expression on CD14+ monocytes by interferon-α in PBC patients - Su, Xi; Jin, Wenwen; Liu, Lizhi; Zhu, Zifei; Li, Cunyan (Frontiers in Immunology, 2023)
Background: The pathogenesis of primary biliary cholangitis (PBC) has yet to be entirely understood. CD47/signal-regulatory protein alpha (SIRPα) is closely related to developing autoimmune diseases by promoting inflammatory response. However, the effect of CD47/SIRPα on inflammatory response in PBC patients is still unclear.Objective: We investigated the expression of CD47/SIRPα and the effect of inflammatory cytokines on the CD47 expression, analyzed potential autoantibodies against CD47 and the effect of anti-CD47 antibody on the inflammatory response in PBC.The expression levels of CD47 and SIRPα on peripheral blood mononuclear cells (PBMC) were measured in 14 patients with PBC (the PBC group) and 13 healthy subjects (the Control group) by flow cytometry (FCM). The PBMC derived from healthy subjects were stimulated with healthy subjects' serum, PBC patients' serum, IFN-α or TNF-α, and the CD47 expression level on CD14 + monocytes was detected by FCM. The level of serum anti-CD47 antibody or IFN-α in PBC patients and healthy subjects was analyzed by ELISA. FCM was used to examine the TNF-α expression level in CD14 + monocytes of healthy subjects stimulated with isotype control antibody, anti-CD47 antibody, LPS or LPS combined with CD47 antibody.The CD47 expression level on the CD14 + monocytes in PBC patients was statistically higher than that in the Control group (P<0.01). Compared with the Control group (PBMC+healthy serum), the CD47 expression on CD14 + monocyte stimulated with the PBC patients' serum (PBMC+PBC patients' serum) was increased (P<0.001); the CD47 expression on CD14 + monocyte stimulated with IFN-α (PBMC + IFN-α) increased gradually with the increased concentration of IFN-α (P<0.05). The levels of serum anti-CD47 antibody and IFN-α in the PBC patients were higher than those in healthy subjects (P<0.05). The TNF-α expression level in CD14 + monocyte stimulated with the anti-CD47 antibody + LPS was higher than that with the LPS (P< 0.05).The CD47 may be related to the pathogenesis of PBC by inflammatory response. The CD47/SIRPα signal were imbalanced in PBC patients. The presence of serum anti-CD47 antibodies in PBC patients provides a laboratory basis for clinical diagnosis and treatment.